1984
DOI: 10.1139/b84-257
|View full text |Cite
|
Sign up to set email alerts
|

Breeding relationships among several species of Agaricus

Abstract: 1984. Breeding relationships among several species of Agaricus. Can. J. Bot. 62: 1884-1889. We have examined the breeding behavior of several species of Agaricus including the cultivated A. brur~nescerls and the wild A. bitorquis, A. vaporarius, A. nrvensis, A. campestris, A. silvicoln, and A. placorn~~ces. For A. brunnescens, two homokaryons carrying auxotrophic mutations and compatible mating types were obtained from the American Type Culture Collection. A stable, prototrophic heterokaryon was recovered by n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…Compatibility group II isolates often exhibited a barrage in incompatible pairings. Similar incompatibility interactions have been described for other Agaricus species (1,17,37).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Compatibility group II isolates often exhibited a barrage in incompatible pairings. Similar incompatibility interactions have been described for other Agaricus species (1,17,37).…”
Section: Discussionsupporting
confidence: 81%
“…Single-spore isolates from a collection identified as A. arvensis produced mating reactions among single-spore progeny, but were later shown to interact with several other Agaricus collections, including A. bitorquis (1,43). The tentative nomenclature of such collections in previously published work, which does not include detailed taxonomic data, should therefore be regarded with caution.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Isozymes were used to discriminate among genotypic classes of A. bisporus, to con¢rm crosses between lines, and to identify new alleles and new genotypes in a wild population [2,3]. Recombinant DNA technology has been used to analyse breeding relationships among several species of Agaricus, to study relationships between A. bisporus and Agaricus bitorquis, to monitor crosses among homokaryons from commercial and wild collected strains [4,5], to detect the presence of DNA polymorphisms in commercial and wild strains of A. bisporus [6], and to construct the ¢rst genetic linkage map in Agaricus [7]. Random ampli¢ed polymorphic DNA (RAPD) markers have been used to ¢ngerprint commercial and wild strains of A. bisporus, while sequence-characterised ampli¢ed sequences ( [8]) have been used to study the inheritance of cap colour in the course of Agaricus breeding programmes [9].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent review Zolan (1995) has suggested that complete chromosome loss can occur if that chromosome is not required for growth. In A. bisporus heterokaryons, 2-25 nuclei can exist in a hyphal cell (Anderson et al, 1984). Therefore, each hyphal cell would contain at least two compatible nuclei.…”
Section: Chromosome Changes In Agaricus Bisporusmentioning
confidence: 99%